Exchange Rate Determinants in Russia : 1992-1993 - Koen, Vincent; Meyermans, Eric. (Washington, D.C. : International Monetary Fund, 1994)
This paper examines the evolution of the exchange rate of the ruble vis-a-vis the U.S. dollar from exchange rate unification, in July 1992, to the end of 1993. The expected and actual paths of the exchange rate are related to the exchange and trade regime and to the stance of financial and exchange rate policies. An econometric analysis based on weekly data is offered, which suggests that monetary factors have a significant impact on the short run behavior of the exchange rate.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet